Around the World with Words: Lessons from 17th Century Malay Dictionary - Othman, Nor Azizah (Melayu: Jurnal Antarabangsa Dunia Melayu, 2022)
The attention of the English in the 17th century towards the development of the Malay language can be presumed as a part of fierce competition between them and their rival, the Dutch (VOC). This stiff competition was not only limited to the monopoly of trade, but also territorial disputes, support from local governments as well as trading advantages. All these environmental factors influenced the English involvement in the production of texts in the Malay language, such as dictionaries, travelogues, religious books and other manuscripts that describe the race, language and land at the time. Thomas Bowrey (TB), for example, was a British merchant who sailed in the Malay Archipelago in the 17th century and became renowned for publishing the first English-Malay dictionary in 1701. Bowrey also produced other works on the Malay language, compiling enormous information about Malay civilization and policy in the 17th century as well as the role, attention and interest of the English in the effort to illustrate the development of the time. This paper discusses proof of the evolution and policy of the Malay civilization in Bowrey’s manuscript. The discussion focuses on navigation jargon in the manuscript. The data are discussed based on etymology approach (Collins, 2003 & 2018). This paper concludes that the data in Bowery’s manuscript show the attention and curiosity of the English towards the Malay language that did not only emerge because of the attestation by the EIC, but also because of the scientific environment and scholarship of the Malay language and people in the 17th century. Full text : PDF